1996
DOI: 10.1182/blood.v87.5.1985.bloodjournal8751985
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of cerebrospinal fluid soluble CD27 levels in patients with meningeal localization of lymphoid malignancies [published erratum appears in Blood 1996 Oct 1;88(7):2818]

Abstract: Diagnosis of meningeal localization of lymphoid malignancies by means of cytologic examination of the cerebrospinal fluid (CSF) can be difficult. Thus far no reliable CSF tumor markers have been identified. CD27 is a transmembrane disulfide-linked 55-kD homodimer present on most peripheral blood T cells and on a subset of B cells. CD27 is also expressed on human malignant B cells and high levels of soluble CD27 can be present in the serum of patients with B-cell malignancies. The aim of this study is to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…From the findings of somatic mutations without ongoing mutation, it seemed likely that at least most of our lymphomas were derived from post-GC cells, in particular from memory cells. Consistent with this consideration, some previous studies 40,41) have shown a high level of soluble CD27, a memory cell marker, 16) in the cerebrospinal fluid of all 40) or most 41) brain lymphoma patients examined. In a few brain lymphoma cases, however, a flow cytometry study 42) failed to detect lymphoma cells positive for CD10, a GC cell marker.…”
Section: Discussionsupporting
confidence: 79%
“…From the findings of somatic mutations without ongoing mutation, it seemed likely that at least most of our lymphomas were derived from post-GC cells, in particular from memory cells. Consistent with this consideration, some previous studies 40,41) have shown a high level of soluble CD27, a memory cell marker, 16) in the cerebrospinal fluid of all 40) or most 41) brain lymphoma patients examined. In a few brain lymphoma cases, however, a flow cytometry study 42) failed to detect lymphoma cells positive for CD10, a GC cell marker.…”
Section: Discussionsupporting
confidence: 79%
“…CD27, a lymphocyte-specific member of the TNF-receptor family, is a transmembrane glycoprotein expressed on T-lymphocytes as well as on normal and malignant B-lymphocytes. Kersten et al (1996) demonstrated a sensitivity of 100% and specificity of 82% for sCD27 in detection of leptomeningeal disease in acute lymphoblastic leukaemia as well as non-Hodgkin lymphoma. However, there is some concern regarding the specificity of sCD27 measurements in CNS lymphomas dealing with its increased expression on activated T and B-cells during infectious and inflammatory CNS diseases (Hintzen et al, 1991;Murase et al, 2000).…”
Section: Cerebrospinal Fluid Analysismentioning
confidence: 98%
“…However, their routine application in standard clinical practice of lymphoma diagnosis still remains to be established. A soluble form of CD27 (sCD27) has been described as a marker of CSF involvement of lymphoid malignancies including PCNSL (Kersten et al, 1996;Murase et al, 1998). CD27, a lymphocyte-specific member of the TNF-receptor family, is a transmembrane glycoprotein expressed on T-lymphocytes as well as on normal and malignant B-lymphocytes.…”
Section: Cerebrospinal Fluid Analysismentioning
confidence: 99%
“…In HIV-positive patients with CNSL, Epstein-Barr virus (EBV) DNA in the CSF may be used as a diagnostic biomarker (34). In HIV-negative patients, several diagnostic biomarkers, including interleukin (IL)-10, IL-6, CXC chemokine ligand-13 (CXCL13), neopterin, β2-microglobulin (β2-MG), osteopontin, soluble CD27, specific microRNAs and cell-free DNA, have been described (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Soluble transmembrane activator and CAML interactor, and soluble B-cell maturation antigen in the CSF have also been identified as promising novel biomarkers for the diagnosis and treatment monitoring of PCNSL (46).…”
Section: Diagnosismentioning
confidence: 99%